Documento sonoro como patrimônio arquivístico documental: um ambiente de descrição, difusão e acesso para o museu antropológico diretor pestana - Maldaner, Sandra Schinwelski (2016)
The Anthropological Director Pestana Museum (MADP), maintained Integration Foundation, Development and the Northwest Education (FIDENE), a private institution of technical and educational-cultural character, becomes part of the development environment of this study with respect to the collection sound made cassette tapes. This file gathers historical documentation Integration Foundation, Development and Education of the Rio Grande do Sul state Northwest - FIDENE installation of FAFI in 1956, the establishment of FIDENE in 1969 and the recognition of UNIJUI in 1985, the regionalization of this in 1993, continued until the present day. The historical building of this institution, as well as custody audio collection and preserved, justify the conduct of this research, while these sound documents require special care and handling, linked to life expectancy of magnetic tape directly attached to the support and technological obsolescence. This research aims to investigate the light of current references of typological identification and the consequent integration of sound documents in the Classification Plan, the methodology and the definition of an arrangement of systematic and preservation for the sound collections generated from scanning cassettes of the Anthropological Museum Director Pestana - MADP belonging to FIDENE File. The need to discuss the inclusion of sound documents in archival management programs part of the whole document assumption is a registration unit independent support information, and the sound file is integrated by sound recordings resulting from public institutions activities, private, person or family in the performance of their activities and regardless of the nature of the support. The motivation for this study is in line with Resolution No. 41 of Conarq - provide for the inclusion of audiovisual, iconographic, sound and musical documents in archival document management programs for their preservation and access. To accomplish this goal, the diagnosis of the sound collection was performed in order to verify the organization and arrangement of these documents. The theoretical framework of this research was based on the themes cultural heritage, archival sound document - cassette, archival description and standardization, dissemination and access, digital preservation and conservation strategies, reliable digital archival repositories and contemporary diplomatic. The foundation of this research consisted in the identification of funds and the use of typological identification of concepts to define the species and preparation of documentary arrangement framework that culminated in the development of research tools Guide, Inventory and catalog in an electronic environment via ICA AtoM. It is an applied research, qualitative approach, conducted through desk research and direct observation, and on the technical procedures consisted in a case study. This research allowed to work out an arrangement framework and establish an arrangement systematically for sound documents FIDENE file and prepare to master product research instruments guide, inventory and catalog to access and dissemination and available online at ICA-AtoM platform documents sound.